Engineering safe anti-CD19-CD28ζ CAR T cells with CD8a hinge domain in serum-free media for adoptive immunotherapy - Muthuganesh Muthuvel; Muthuganesh Muthuvel; Thamizhselvi Ganapathy; Trent Spencer; Sunil S. Raikar; Saravanabhavan Thangavel; Alok Srivastava; Alok Srivastava; Alok Srivastava; Sunil Martin (Frontiers in Immunology)
BackgroundDespite the curative potential, high cost of manufacturing and the toxicities limits the wider access of Chimeric Antigen Receptor (CAR) T cell therapy in global medicine. CARs are modular synthetic antigen receptors integrating the single-chain variable fragment (scFv) of an immunoglobulin molecule to the TCR signaling. CARs allow HLA independent, T cell mediated destruction of tumor cells independent of tumor associated-HLA downregulation and survive within the patient as ‘living drug.’ Here we report a safer approach for engineering alpha beta T cells with anti- CD19-CD28ζ CAR using self-inactivating (SIN) lentiviral vectors for adoptive immunotherapy.Methodαβ T cells from the peripheral blood (PB) were lentivirally transduced with CAR construct containing hinge domain from CD8α, transmembrane and co-stimulatory domain from CD28 along with signaling domain from CD3ζ and driven by human UBC promoter. The cells were pre-stimulated through CD3/CD28 beads before lentiviral transduction. Transduction efficiency, fold expansion and phenotype were monitored for the CAR T cells expanded for 10–12 days. The antigen-specific tumor-killing capacity of CD19 CAR T cells was assessed against a standard CD19 expressing NALM6 cell lines with a flow cytometry-based assay optimized in the lab.Results and conclusionWe have generated high titer lentiviral vectors of CAR with a titer of 9.85 ± 2.2×107 TU/ml (mean ± SEM; n=9) generating a transduction efficiency of 27.57 ± 2.4%. (n=7) at an MOI of 10 in total T cells. The product got higher CD8+ to CD4+ CAR T cell ratio with preponderance of an effector memory phenotype on day 07 and day 12. The CAR-T cells expanded (148.4 ± 29 fold; n=7) in serum free media with very high viability (87.8 ± 2.2%; n=7) on day 12. The antitumor functions of CD19 CAR T cells as gauged against percentage lysis of NALM6 cells at a 1:1 ratio is 27.68 ± 6.87% drawing up to the release criteria. CAR T cells produced IFNγ (11.23 ± 1.5%; n=6) and degranulation marker CD107α (34.82 ± 2.08%; n=5) in an antigen-specific manner. Furthermore, the sequences of WPRE, GFP, and P2A were removed from the CAR construct to enhance safety. These CAR T cells expanded up to 21.7 ± 5.53 fold with 82.7±5.43% viability (n=4).ConclusionWe have generated, validated, and characterized a reproducible indigenous workflow for generating anti-CD19 CAR T cells in vitro. This approach can be used for targeting cancer and autoimmune diseases in which CD19+ B lineage cells cause host damage.